Impact of Recession on the employment in Catalonia from a gender and age perspective - Ma.Jesus Gomez Adillon; M.Angels Cabases Pique; Agnes Pardell Vea (European Regional Science Association (ERSA), 2016)
In Catalonia, between 2008 and 2014, the rate of youth unemployment has exponentially increased and it has turned into a structural problem: when the fourth quarter of 2014 ended, among the people under the age of 30, the number of unemployed people was 1,495,600, 645,000 more than in the first quarter of 2008. In addition, with the data provided by the Spanish Tax Agency, the average wage of wage earners over 25 years in 2014 is 3.4 times superior to the young people and the reduction of the average wage of these is 2.8 times bigger. Moreover, during this period, the annual income of women has shortened the distance in relation to men, mainly the employed group, from a ratio of 1.40 to 1.30, but in contrast, the number of women receiving minimal resources (MW and MP) has worsened: in relation to employees, 31.7% of the total number within this subgroup. In order to highlight the uneven impact of recession on the labor market in Catalonia, this study examines the evolution of its main variables in the period 2008-2014 from a gender and age perspectives delving into the structure wages and analyzing the distribution of inter-group and intra-group inequality between men and women.
Keywords: E24; J21; J31; E3; 330; labor market; wages; youth; gender inequality